Penerapan Teaching Game for Understanding terhadap Hasil Belajar Permainan Bola Voli - Fahmi Hadi Sebila; Nurlan Kusmaedi; Tite Juliantine (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This research aims to examine the effect of the Teaching Game For Understanding (TGFU) learning model by using a modified ball to hours volleyball learning outcomes. The participants of this study were Social Sciences students of SMA Negeri 3 Sukabumi City, as many as 90 students were divided into 3 groups. The first group of students who were given TGFU treatment with a modified ball, the second TGFU with normal ball, and the third group without treatment. The method used in this research is The Matching-Only pre-test-posttest control group design and teaching with ball modification. The instrument used in this study are the GPAI. The results of this study (1) there is a development of the volleyball game results with the TGFU learning model using a modified ball (2) there is no development of volleyball game results with the TGFU learning model using normal balls. In conclusion, the delivery of the TGFU learning program using modified balls increases volleyball learning outcomes. Keywords: Teaching Game for Understanding, Volleyball.